GLOBE at Night in China. (5th March 2015) - Guo, Hongfeng
Abstract: The GLOBE at Night citizen-science campaign was introduced in China in 2010. Observations and works made by students are presented. The students were guided to participate in this meaningful international activity by 1) taking light pollution observations of the night sky at different locations, 2) becoming aware of the severity of the effects of light pollution, and 3) making the whole society aware of the importance to save energy by reducing light pollution.